(untitled) (The Review of Diabetic Studies, 2017)
Transplantation of pancreatic islets encapsulated within immuno-protective microcapsules is a strategy that has the potential to overcome graft rejection without the need for toxic immunosuppressive medication. However, despite promising preclinical studies, clinical trials using encapsulated islets have lacked long-term efficacy, and although generally considered clinically safe, have not been encouraging overall. One of the major factors limiting the long-term function of encapsulated islets is the host’s immunological reaction to the transplanted graft which is often manifested as pericapsular fibrotic overgrowth (PFO). PFO forms a barrier on the capsule surface that prevents the ingress of oxygen and nutrients leading to islet cell starvation, hypoxia and death. The mechanism of PFO formation is still not elucidated fully, and studies using a pig model have tried to understand the host immune response to empty alginate microcapsules. In this review, the varied strategies to overcome or reduce PFO are discussed, including alginate purification, altering microcapsule geometry, modifying alginate chemical composition, coencapsulation with immunomodulatory cells, administration of pharmacological agents, and alternative transplantation sites. Nanoencapsulation technologies, such as conformal and layer-by-layer coating technologies, as well as nanofiber, thin-film nanoporous devices, and silicone-based NanoGland devices are also addressed. Finally, this review outlines recent progress in imaging technologies to track encapsulated cells, as well as promising perspectives concerning the production of insulin-producing cells from stem cells for encapsulation.